The role of Helicobacter pylori infection in skin disorders - Abd-Alrahman, Tasneem Z.; Aboud, Rana S.; Al-Ahmer, Saife D.; Muhammad, Talib Y. (Iraqi Journal of Science, 2022)
This study was amied to determine the relationship between Helicobacter pylori infection and skin disorders, sixty six patients who suffering from skin diseases (Urticaria and atopic dermatitis) who attended at Dermatological Clinic Al-Numan Teaching Hospital. Aged (6--62) years have been investigated and compared to Twenty two samples of apparently healthy individual's were studied as control group . All the studied groups were subjected to measurement of anti- Helicobacter pylori antibodies IgA by Enzyme linked immunosorbent assay (ELISA). The results of current study revealed that there were a significant elevation (P<0.05) in the concentration of H. pylori IgA antibodies in sera of patients with chronic urticaria and atopic dermatitis compared to control group, and there were non significant differences (P>0.05) in the concentration of H. pylori IgA Ab in sera of patients according to the ages and gender. Conclusion, Helicobacter pylori may have a role in the pathogenesis of chronic urticaria and atopic dermatitis, and the results of present study suggest that H.pylori infection should be included in diagnostic workup of patients with skin disorders.